2017
DOI: 10.1002/2016jd025663
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing evidence of decadal changes in major tropospheric ozone precursors over East Asia

Abstract: Recent regulatory policies in East Asia reduce ozone precursors, but these changes are spatially and temporally nonuniform. This study investigates variations in the long‐term trends of tropospheric NO2, HCHO, and HCHO/NO2 ratios to diagnose ozone sensitivity to changes in NOx and volatile organic compound using the Ozone Monitoring Instrument (OMI). Using an adaptive‐degree polynomial filter, we identify extremums of time series of NO2 to determine when and how NO2 change. Due to the regulations in China, tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 63 publications
14
66
0
Order By: Relevance
“…In addition to installing denitration devices at power plants and cement plants, China has transformed its industrial structure by phasing out heavily polluting industrial factories, decreasing coal consumption, controlling vehicle emissions through stricter emission standards and scrapping aged vehicles. The average emission trend fitted by this study is consistent with the previous findings, which showed that OMI NO 2 levels peaked in 2011 over China Duncan et al, 2016) and NO x emissions from satellite data assimilation peaked in 2011/2012 (Miyazaki et al, 2017;van der A et al, 2017;Souri et al, 2017), respectively. Additionally, the fitted emission peaks for individual cities showed reasonable agreement with the peaks of OMI NO 2 levels at provincial level (Liu et al, 2016b).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In addition to installing denitration devices at power plants and cement plants, China has transformed its industrial structure by phasing out heavily polluting industrial factories, decreasing coal consumption, controlling vehicle emissions through stricter emission standards and scrapping aged vehicles. The average emission trend fitted by this study is consistent with the previous findings, which showed that OMI NO 2 levels peaked in 2011 over China Duncan et al, 2016) and NO x emissions from satellite data assimilation peaked in 2011/2012 (Miyazaki et al, 2017;van der A et al, 2017;Souri et al, 2017), respectively. Additionally, the fitted emission peaks for individual cities showed reasonable agreement with the peaks of OMI NO 2 levels at provincial level (Liu et al, 2016b).…”
Section: Discussionsupporting
confidence: 81%
“…Several recent studies (e.g., Duncan et al, 2016;Krotkov et al, 2016) have suggested the effectiveness of the air quality policy, as evidenced by a decreasing trend in NO 2 columns over China since 2012. Miyazaki et al (2017), van der A et al (2017), and Souri et al (2017) have further reported a recent decline in national NO x emissions on the basis of satellite data assimilation. Liu et al (2016b) have studied changes in NO 2 column densities for each province from 2005 to 2015 and have performed an intercomparison of a bottom-up inventory and satellite observations; the study attributes the decline in regional NO 2 to decreased emissions from power plants and urban vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…However, isoprene is still one major reason accounting for high-level HCHO columns because it is more active than anthropogenic VOCs. Further, anthropogenic VOCs might impose substantial impacts as well [20]. As reported, a continuous growth trend of China's historical NMVOCs emissions was found during the period of 1980-2005, with the emission increasing by 4.2 times at an annual average rate of 10.6%; populous cities, covering merely 4.5% of China's territory, accounted for 24.9% of the national emissions [51].…”
Section: Analyses Of Potential Factors For the Hcho Summertime Concenmentioning
confidence: 86%
“…Fu et al proposed a linear function relating HCHO and VOCs and analyzed the distribution of HCHO in South and East China through a continuous 6-year record (1996)(1997)(1998)(1999)(2000)(2001) of GOME satellite measurements [4]. Jin et al and Souri et al also studied the distribution of HCHO throughout China, but only as a component of a larger research experiment [6,20]. However, more thorough investigations focused on Beijing-Tianjin-Hebei are still required urgently.…”
Section: Introductionmentioning
confidence: 99%
“…Over this decade, some areas have seen increases, such as India (Lu and Streets, 2012), the Canadian oil sands region (McLinden et al, 2015), and other oil extraction regions , while areas such as the eastern US (Russell et al, 2012;Lamsal et al, 2015;de Foy et al, 2016a) and Europe (Curier et al, 2014;Duncan et al, 2016) have seen large decreases due to a switch to cleaner fuels and the implementation of emission control technologies. Over this 10-year period, China has seen a reversal of its trends: during 2005-2010 OMI NO 2 tropospheric columns were increasing (Verstraeten et al, 2015), in 2011-2012 they had stabilized (Souri et al, 2017), and since 2012 they have subsequently decreased as the country enforces its 12th 5-year plan (de Foy et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%